An algorithm for construction of ?-value functions for the Bolza control problem - Jacewicz, Edyta (Zielona Góra: Uniwersytet Zielonogórski)
The problem considered is that of approximate numerical minimisation of the non-linear control problem of Bolza. Starting from the classical dynamic programming method of Bellman, an ?-value function is defined as an approximation for the value function being a solution to the Hamilton-Jacobi equation.
Keywords: non-linear optimisation; Bolza problem; optimal control; Hamilton-Jacobi equation; dynamic programming; approximate minimum